Frontiers in Materials Processing, Applications, Research and Technology Select Proceedings of FiMPART 2015 - Muruganant, M.; Chirazi, Ali; Raj, Baldev (Springer Nature Singapore : Imprint: Springer, 2018)
This volume comprises the select proceedings of FiMPART 2015. The volume covers advances in major areas of materials research under one umbrella. This volume covers all aspects of materials research, processing, fabrication, structure/property evaluation, applications of ferrous, non-ferrous, ceramic, polymeric materials and composites including biomaterials, materials for energy, fuel cells/hydrogen storage technologies, batteries, super-capacitors, nano-materials for energy and structural applications, aerospace structural metallic materials, bulk metallic glasses and other advanced materials. The book will be useful to researchers, students, and professional working in areas related to materials innovation and applications.